Right subclavian vein approach for selective left bundle branch pacing: A case report. Issue 1 (29th July 2022) - Peng, Xinhui; Jiang, Longfu; Chen, Sujun; Feng, Haiming
Abstract: We reported a 65‐year‐old man with symptomatic bradycardia caused by chronic atrial fibrillation who underwent pacemaker implantation by left bundle branch pacing (LBBP) via right subclavian vein (RSV) approach. A tricuspid valve annulus (TVA) angiography was performed, and a different connecting cable that can monitor electrocardiograms (ECG) and intracardiac electrograms (EGM) in real time was used during the process. By TVA angiography, we could easily find the ideal location of LBBP; a new connecting cable helped us avoid perforation and guide effective endpoint without the need to stop pacing. The case showed that it was feasible and safe to use the new method for LBBP through RSV route. Abstract : Imaging of pacing implantation process in the left bundle branch region of the right subclavian vein approach. Characteristics of left bundle branch capture during the screwring procedure using a novel connecting cable.